2017
DOI: 10.1371/journal.pbio.2000731
|View full text |Cite
|
Sign up to set email alerts
|

Lung Basal Stem Cells Rapidly Repair DNA Damage Using the Error-Prone Nonhomologous End-Joining Pathway

Abstract: Lung squamous cell carcinoma (SqCC), the second most common subtype of lung cancer, is strongly associated with tobacco smoking and exhibits genomic instability. The cellular origins and molecular processes that contribute to SqCC formation are largely unexplored. Here we show that human basal stem cells (BSCs) isolated from heavy smokers proliferate extensively, whereas their alveolar progenitor cell counterparts have limited colony-forming capacity. We demonstrate that this difference arises in part because … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 74 publications
0
33
0
Order By: Relevance
“…The transcriptome of lung basal cells most closely correlates with the transcriptional profile of human lung SqCC [46]. Indeed, landmark studies have revealed that different lung cancer subtypes arise from distinct lung epithelial cell lineages [47,48], suggesting that basal cells are the cells-of-origin of lung SqCC [49].…”
Section: Squamous Cell Carcinomamentioning
confidence: 98%
“…The transcriptome of lung basal cells most closely correlates with the transcriptional profile of human lung SqCC [46]. Indeed, landmark studies have revealed that different lung cancer subtypes arise from distinct lung epithelial cell lineages [47,48], suggesting that basal cells are the cells-of-origin of lung SqCC [49].…”
Section: Squamous Cell Carcinomamentioning
confidence: 98%
“…These models have been successfully established for solid tumors, including breast, melanoma, prostate, and pancreatic cancers and have been shown to recapitulate the phenotype, molecular profile, and therapeutic response of the patient's tumors (17)(18)(19). PDXs therefore constitute a highly clinically relevant system to study human solid tumors, even more specifically in lung cancer where whole genome sequencing analyses have revealed the complex heterogeneity and high frequency of genetic alterations in lung SqCC (20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%
“…To further investigate the role of BCL11A in LUSC, we employed a recently described 3D organoid culture system for basal cells (BCs) from the trachea, as they have been suggested to be the cell of origin for LUSC 20 . BCs from human and mouse lungs have higher expression of BCL11A when compared to the other epithelial compartments (Supplementary Figure 4a and b) 21 . Therefore, we crossed the BCL11A ovx mice to R26-CreERT2 mice, which allowed us to induce Cre recombination by the administration of tamoxifen.…”
Section: Mainmentioning
confidence: 99%
“… (a) RNA-Seq data analysed from Weeden et al 21 indicating that in human samples FACS fraction labelled as proximal BCs has approximately 400 fold increase in human BCL11A levels in comparison to other epithelial fractions. (b) RNA-Seq data from the same dataset indicating that mouse Bcl11a is approximately 500-1000 fold higher in basal fractions compared to other epithelial subtypes.…”
Section: Mainmentioning
confidence: 99%